Pengaruh Job Enrichment, Budaya Organisasi dan Komunikasi Organisasi terhadap Kinerja Karyawan pada PT. Semen Padang - Sonia Rahmayani; M. Afuan; Bayu Pratama Azka (Jurnal Bintang Manajemen, 2025)
This study aims to find out and try to analyze how much the Influence of Job Enrichment, Organizational Culture and Organizational Communication on Employee Performance at PT. Semen Padang. The data analysis method used a questionnaire, with a sample of 75 people with a population and a sample of PT. Semen Padang. The data analysis method uses structural equation modeling (SEM) with the SmartPLS 4.1 analysis tool. The results of the study found that there was a significant influence between Job Enrichment and Employee Performance. There is a significant influence between Organizational Culture and Employee Performance. There is a significant influence between organizational communication and employee performance.